Thermoluminescence Dosimeters Holder Cassette Design and 3D Printing - TUNÇMAN, Duygu; KESMEZACAR, Fahrettin Fatih; GÜNAY, Osman; YEYİN, Nami and DEMİR, Özge and DEMIR, Mustafa and AKKUŞ, Baki (International Journal of Computational and Experimental Science and Engineering, 2023)
3-dimensional (3D) printing technology has been used in many fields and has taken a significant place in several applications. The ease of production, cheap cost, being able to produce the product most suitable for your needs, and easy accessibility of the 3D printer have enabled it to be used in many areas. This study emerged from the need for an apparatus to place thermoluminescence dosimeters (TLDs) during the calibration of TLDs to be used to determine organ doses in fluoroscopy applications. In the study, the TLD holder cassette that was specially designed in the SolidWorks program was printed from PLA material using the fused deposition modelling (FDM) technique with Creality Ender 3 S1 printer. With this 3D TLD holder cassette that was designed and printed in accordance with the needs, we aimed to show the usability of the 3D printing technique in almost every field of applied sciences.